2019
DOI: 10.1186/s13098-019-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synbiotic bread containing lactic acid on glycemic indicators, biomarkers of antioxidant status and inflammation in patients with type 2 diabetes: a randomized controlled trial

Abstract: BackgroundThe aim of this randomized, double-blinded, controlled trial was to investigate the effect of daily consumption of a synbiotic bread containing lactic acid on glycemic status, antioxidant biomarkers and inflammation in patients with type 2 diabetes (T2D).MethodsT2D patients, aged 20 to 60 years, were randomly assigned to consume synbiotic + lactic acid (n = 30), synbiotic (n = 30), lactic acid (n = 30), or control (n = 30) bread for 8 weeks. Patients consumed bread 3 times a day in a 40 g package for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
(33 reference statements)
0
27
0
1
Order By: Relevance
“…Asemi et al reported that a single species synbiotic mixture of Bacillus coagulans (previously Lactobacillus sporogenes ) and inulin significantly correlated to hs-CRP level changes from baseline of –1.057 ± 0.283 mg/L compared to a slight mean increase of 0.0054 ± 0.385 mg/L in control, whereas another intervention group from a study using B. coagulans and inulin rich bread presented a significant change of –689.76 ± 368.98 μg/L compared to an increase of 33.80 ± 237.60 μg/L in a control group consuming lactic acid-enriched bread ( 156 , 157 ). Similar studies investigating the effects of single species synbiotics using other formulations of B. coagulans and inulin have all showed a trend of decrease in the levels of either CRP or hs-CRP, although these results were not significant ( 157 159 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Asemi et al reported that a single species synbiotic mixture of Bacillus coagulans (previously Lactobacillus sporogenes ) and inulin significantly correlated to hs-CRP level changes from baseline of –1.057 ± 0.283 mg/L compared to a slight mean increase of 0.0054 ± 0.385 mg/L in control, whereas another intervention group from a study using B. coagulans and inulin rich bread presented a significant change of –689.76 ± 368.98 μg/L compared to an increase of 33.80 ± 237.60 μg/L in a control group consuming lactic acid-enriched bread ( 156 , 157 ). Similar studies investigating the effects of single species synbiotics using other formulations of B. coagulans and inulin have all showed a trend of decrease in the levels of either CRP or hs-CRP, although these results were not significant ( 157 159 ).…”
Section: Resultsmentioning
confidence: 94%
“…The effect of synbiotics on SOD levels in diabetics were investigated by three studies, all of whom have reported an increasing effect following intervention ( Table 4 ). Ghafouri et al reported significant rise in SOD levels of + 0.40 ± 0.13 and + 0.87 ± 0.22 mmol/L following an 8-week supplementation with bread containing single-species probiotics without and with lactic acid, respectively ( 157 ). Mirmiranpour et al presented a statistically insignificant increase of 0.14 U/mL in mean SOD levels between the two groups ( 144 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synbiotic agents are a combination of prebiotics and probiotics with beneficial effects on host through the enhancement of activity and survival of beneficial microorganisms in the gastrointestinal tract, so that they can selectively provoke the growth and stimulate the metabolism of one or more health-promoting bacteria, thereby enhancing the host welfare [88][89][90][91][92][93][94][95][96][97]. The most The reported key mechanisms of action of probiotics [87] have been mentioned as follows (see Figure 2): enhancement of epithelial barrier, modulation of insulin-sensitive tissues, synthesis of antimicrobial substances, multi-pathogen competition, and induction of mucin secretion.…”
Section: Synbioticsmentioning
confidence: 99%
“…In contrast, another meta-analysis of human studies reported that although probiotic intervention had a significant effect on both SBP and DBP measures, it did not affect the LDL-C concentration in patients with T2DM [ 20 ]. In a randomized controlled trial study, probiotic intervention was shown to have a significant effect on TAC measures in patients with T2DM [ 21 ], while other studies found no significant effects [ 17 , 18 ]. Our previous findings also showed a significant improvement in serum glucose and HDL-C measures following probiotic supplementation, while no significant changes were seen in the levels of serum TC [ 22 ].…”
Section: Introductionmentioning
confidence: 99%